Assessment of aortocoronary bypass grafting using exercise ST segment/heart rate relation. Issue 4 (April 1984) - Kardash, M M; Boyle, R M; Watson, D A; Stoker, J B; Mary, D A; Linden, R J
Abstract : The maximal rate of progression of ST segment depression relative to increases in heart rate (maximal ST/HR slope) has recently been shown to be an accurate index of the presence and the severity of coronary heart disease in patients with angina. The value of this new exercise test was assessed in patients undergoing aortocoronary bypass. The maximal ST/HR slope and the results of coronary angiography were obtained in each of 46 patients before aortocoronary bypass surgery and in 26 of the 46 patients six months after the operation. At each stage of the investigation the maximal ST/HR slope detected without false results the absence and the number of significantly diseased vessels as shown by angiocardiography. As in previous findings the ranges of the maximal ST/HR slope showed no overlap between the four groups of patients: those with no significant disease and those with single, double, or triple vessel disease. In each of the 46 patients in whom the maximal ST/HR slope was determined before operation and three months afterwards the slope was lower after operation than before, indicating improvement. Follow up examinations showed that the maximal ST/HR slopes accurately detected the number of patent grafts used to bypass significantly diseased coronary arteries. Furthermore, the development of a significant narrowing or occlusion in any vein graft caused an increase in the maximal ST/HR slope which was equivalent to the value of single vessel disease. It is suggested that the maximal ST/HR slope may be used reliably in individual patients to indicate restoration of adequate blood supply to the myocardium after successfully aortorcoronary bypass surgery and the to detect in the period of six months after the operation the degree of severity of coronary heart disease whether it is caused by occlusion of the graft of significant disease of the coronary arteries.